180° magnetization switching in nanocylinders by a mechanical strain. (June 2015) - Yi, Min; Xu, Bai-Xiang; Shen, Zhigang
Abstract: The magnetization switching dynamics in ferromagnetic Cobalt nanocylinders under mechanical loading is studied by a constraint-free phase field model, which allows the exactly constant magnetization magnitude and the explicit magneto-mechanical coupling. Results show that the single-domain switching mode, which is of great interest for memory technologies, exists only in small nanocylinders, and the critical radius is found to be around 8 nm. Furthermore, a novel mechanical loading and unloading scheme, which makes use of the overrun of magnetization during the precessional switching, is proposed to achieve a deterministic 180 ° switching. The 180 ° switching is driven firstly by the magneto-mechanical coupling and then by the magnetocrystalline anisotropy ( K u ). The threshold strain to induce the deterministic switching increases with K u . The switching time firstly decreases with increasing strain rapidly and then saturates. The results shed light on the design of an optimum mechanically driven nanomagnets-based logic and memory devices.